2013
DOI: 10.1155/2013/217261
|View full text |Cite
|
Sign up to set email alerts
|

ERCP Features and Outcome in Patients with Periampullary Duodenal Diverticulum

Abstract: Background. Although periampullary diverticulum is usually asymptomatic and discovered incidentally in patients during endoscopic retrograde cholangiopancreatography (ERCP), it may lead to post-ERCP morbidity. We compared baseline characteristics and clinical data as well as ERCP results in patients with and without periampullary diverticulum. Methods. Clinical, laboratory, and ERCP data of 780 patients referred to the Taleghani Hospital, as a great referral endoscopy center, in Iran were prospectively analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 15 publications
(21 reference statements)
3
26
0
Order By: Relevance
“…It is reported in the literature that stones in the common bile duct occur significantly more often in patients with diverticuli [12, 13], indicating that the anatomical abnormality and malfunction of the sphincter of Oddi possibly play an important role in the formation of stones [14]. Also periampullary diverticuli are associated with larger stones and severe cholangitis [15, 16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported in the literature that stones in the common bile duct occur significantly more often in patients with diverticuli [12, 13], indicating that the anatomical abnormality and malfunction of the sphincter of Oddi possibly play an important role in the formation of stones [14]. Also periampullary diverticuli are associated with larger stones and severe cholangitis [15, 16].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, this is not the case. ERCP appeared to be a safe procedure also in patients with diverticuli, with a good success rate and low complications [1, 10, 13], although there is one study reporting more post-ERCP pancreatitis [11]. …”
Section: Discussionmentioning
confidence: 99%
“…Compared to standard cannulation, DWT may replace standard cannulation or become the salvage procedure in cases of unsuccessful biliary cannulation as a result of its high success rate with an acceptable incidence of PEP . For patients with periampullary duodenal diverticulum, DWT may offer a safe and effective method in biliary cannulation compared to TPS …”
Section: Discussionmentioning
confidence: 99%
“…Adverse events included post-ERCP pancreatitis, perforations, cholangitis, and post-procedural bleeding evidenced by a drop-in hemoglobin >2g/dl. All adverse events were defined according to published criteria [14].…”
Section: Data Typementioning
confidence: 99%
“…The first group of studies published in the 1980s and 1990s suggested a significantly higher rate of cannulation's failure in patients with PAD, prolonged procedure time, and an increase in adverse events' rates [10], [11]. The second group of studies showed that there is no significant difference in the cannulation procedure success in case of presence or absence of PAD [12]- [14]. Moreover, recent prospective studies did not reveal any significant difference in either overall adverse events or a specific event, especially PEP [15]- [17].…”
Section: Introductionmentioning
confidence: 99%